Polysplenia Syndrome With Splenic and Skeletal Muscle Metastases From Thyroid Carcinoma Evaluated by FDG PET/CT: Case Report and Literature Review. Issue 4 (January 2016) - Li, Zu-Gui; Lin, Zhi-Chun; Mu, Hai-Yu
Abstract : Abstract: Polysplenia syndrome (PSS) is a rare congenital abnormality. Metastases to spleen and skeletal muscle from differentiated thyroid cancer (DTC) are also extremely rare. Our case report aims to present an interesting case of PSS associated with splenic metastasis (SM) and skeletal muscle metastasis (SMM) from advanced papillary thyroid carcinoma which was evaluated on fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT). An 84-year-old Chinese man was admitted with the history of multiple enlarged masses in bilateral neck, right axillary, and inguinal areas for >2 months. The results of ultrasonography examination were highly suggestive of malignancy. The histological results of the following biopsy were consistent with papillary thyroid carcinoma with involvement of multiple regional lymph nodes. He was referred for an FDG PET/CT imaging to evaluate the situation. FDG PET/CT showed that an intense FDG-avid thyroid mass with widespread regional lymph node involvement and distant metastases in the body. Unexpected sites of metastases were detected in the spleens and skeletal muscles. Most interestingly, FDG PET/CT imaging also described the typical imaging findings of PSS including the 2 right-sided spleens, azygos and hemiazygos continuation of inferior vena cava (IVC), right-sided stomach, middle line liver, a short pancreas, preduodenal portal vein (PPV), and malrotation of gut. Whole body FDG PET/CT imaging can accurately evaluate the situation of DTC by detecting regional lymph node involvement, common and rare sites of distant metastases which are closely related to staging, management, and prognosis of this disease. Whole-body FDG PET/CT is also valuable in demonstrating the typical imaging features of PSS.